Birth experience during COVID-19 confinement (CONFINE): protocol for a multicentre prospective study. Issue 12 (10th December 2020) - Bertholdt, Charline; Epstein, Jonathan; Banasiak, Claire; Ligier, Fabienne; Dahlhoff, Sandra; Olieric, Marie France; Mottet, Nicolas; Beaumont, Marine; Morel, Olivier
Abstract : Introduction: The absence of companionship during childbirth is known to be responsible for negative emotional birth experience, which can increase the risk of postpartum depression and post-traumatic stress disorder. The context of COVID-19 epidemic and the related confinement could increase the rate of negative experience and mental disorders. The main objective is to compare, in immediate post partum, the maternal sense of control during childbirth between a group of women who gave birth during confinement ('confinement' group) versus a group of women who gave birth after confinement but in the context of epidemic ('epidemic' group) versus a group of control women ('control' group; excluding confinement and epidemic context). Methods and analysis: This is a national multicentre prospective cohort study conducted in four French maternity units. We expect to include 927 women in a period of 16 months. Women will be recruited immediately in post partum during three different periods constituting the three groups: 'confinement'; 'epidemic' and 'control' group. The maternal sense of control will be evaluated by the Labour Agentry Scale questionnaire completed immediately in post partum. Postnatal depression (Edinburgh Postnatal Depression Scale), post-traumatic stress disorder (Impact of Event Scale—Revised) and breast feeding (evaluative statement) will be evaluated at 2 months post partum. Ethics and dissemination: The study was approved by the French Ethics Committee, the CPP (Comité de Protection des Personnes) SUD OUEST ET OUTRE-MER IV on 16th of April 2020 with reference number CPP2020-04-040. The results of this study will be published in a peer-reviewed journal and will be presented at relevant conferences. Trial registration number: NCT04348929 .